About the possibility to measure the circular polarization of high-energy photon in reaction γ + e⁻ → e⁺ + e⁻ + e⁻ - Gakh, G.I.; Konchatnij, M.I.; Levandovsky, I.S.; Merenkov, N.P. (Вопросы атомной науки и техники, 2012)
Two possibilities of the measuring high-energy photon circular polarization by means of the process γ + e⁻ → e⁺ + e⁻ + e⁻ are investigated. The first one is connected with the measurement of polarization asymmetry of the cross section when the initial electron beam is longitudinally polarized. The second possibility related with the measurement of the created-positron (or electron) polarization. Just this polarization does not decrease when the photon energy grows up and can be used for effective determination of the photon circular polarization degree. Проанализированы две возможности определения степени циркулярной поляризации высокоэнергетического фотона в процессе γ + e⁻ → e⁺ + e⁻ + e⁻. Первая связана с измерением поляризационной асимметрии сечения, когда начальный пучок электронов обладает продольной поляризацией. Вторая – с измерением поляризации образованного позитрона (или электрона). Показано, что в последнем случае поляризация не убывает с ростом энергии фотона и может быть использована для эффективного определения степени его циркулярной поляризации. Проаналізовано дві можливості визначити ступінь циркулярної поляризації фотона високої енергії у реакції γ + e⁻ → e⁺ + e⁻ + e⁻. Перша пов'язана із вимірюванням асиметрії перерізу, коли початковий пучок електронів має поздовжню поляризацію. Друга -- із вимірюванням поляризації утворюваного позитрона (чи електрона). Виявлено, що в останньому випадку поляризація не зменшується з ростом енергії фотона і може бути використана для ефективного визначення його циркулярної поляризації.